1975
DOI: 10.1002/art.1780180413
|View full text |Cite
|
Sign up to set email alerts
|

Identification of neutral proteases in human neutrophil granules that degrade articular cartilage proteoglycan

Abstract: Human polymorphonuclear neutrophil (PMN) granule extract (25 pg of protein) released 60% of the available 3 5 s 0 , from labeled rabbit articular cartilage in 0.5 hour at neutral pH. N-acetyl-L-alanyl-Lalanyl-L-prolyl-L-alanine chloromethyl ketone (NAc-AAPACK), a specific elastase inhibitor, was only minimally effective against whole granule extract, and Na-tosyl-L-lysine chloromethyl ketone, which inhibits trypsin but not elastase, was completely ineffective. Preparative disc-gel electrophoresis of PMN granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 29 publications
(13 reference statements)
1
33
0
Order By: Relevance
“…Consistent with this hypothesis are the recent findings that mutations within the BP180 gene lead to the inherited blistering disease, generalized atrophic benign epidermolysis bullosa (49). NE degrades collagens (50-53), fibronectin (54), and proteoglycans (55,56). The results of our in vitro enzyme digestion experiments demonstrate that NE also cleaves the extracellular domain of the BP180 protein.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with this hypothesis are the recent findings that mutations within the BP180 gene lead to the inherited blistering disease, generalized atrophic benign epidermolysis bullosa (49). NE degrades collagens (50-53), fibronectin (54), and proteoglycans (55,56). The results of our in vitro enzyme digestion experiments demonstrate that NE also cleaves the extracellular domain of the BP180 protein.…”
Section: Discussionsupporting
confidence: 85%
“…The mol wt of the principal CT isozyme lies between 23,000 and 28,000 daltons, and its amino acid composition has now been described with enzyme derived from both leukemic (35) and normal (18) cells. In an earlier report from this laboratory (15) it was suggested that these two PMN enzymes, E and CT, were the major proteases responsible for degradation of cartilage matrix proteoglycans by human PMN granule extracts (G) at neutral pH. This tentative conclusion was based on the observed solubilization of 'SO4 from slices of rabbit articular cartilage by partly purified protein fractions isolated by preparative acrylamide gel electrophoresis 620 A. Janoff, G. Feinstein, C. J.…”
Section: Discussionmentioning
confidence: 99%
“…This tentative conclusion was based on the observed solubilization of 'SO4 from slices of rabbit articular cartilage by partly purified protein fractions isolated by preparative acrylamide gel electrophoresis 620 A. Janoff, G. Feinstein, C. J. Malemud of G. Only those acrylamide gel fractions containing E or CT were active in releasing the radiolabel (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Massive numbers of neutrophils accumulate in rheumatoid synovial fluids where they may release large amounts of NE [1], a serine proteinase that cleaves proteoglycans and type II collagen, the major constituents of articular cartilage [2,3]. NE is therefore believed to play a significant pathological role in arthritis.…”
Section: Introductionmentioning
confidence: 99%